Overlapping decline in orbitofrontal gray matter volume related to cocaine use and body mass index. (8th August 2013) - Smith, Dana G.; Jones, P. Simon; Williams, Guy B.; Bullmore, Edward T.; Robbins, Trevor W.; Ersche, Karen D.
Abstract Loss of control over hedonically motivated actions is a defining component of impulse control disorders, such as drug dependence and the proposed 'food addiction' model of obesity. Devolution from goal‐directed to compulsively maintained behaviors is partially attributed to abnormalities in the orbitofrontal cortex, an area critical in reward valuation. In the current study, overlapping reductions in orbitofrontal gray matter volume relating to body mass index were seen in healthy control and cocaine‐dependent individuals, as well as in relation to duration of cocaine abuse, providing support for a shared neuropathology between the two conditions potentially related to dysfunctional reward‐seeking behavior.